CA6-based macroporous refractory thermal insulators containing mineralizing agents. Issue 15 (December 2020) - Borges, O.H.; Santos, T.; Salvini, V.R.; Pandolfelli, V.C.
Abstract: Aiming at reducing the temperature of CaO.6Al2 O3 (CA6 ) formation, SiO2, ZnO, and TiO2 were evaluated as mineralizing agents in an Al2 O3 -CaCO3 based macroporous thermal insulator. For the concentrations tested (0.6 mol% to 2.8 mol%), SiO2 presented a small effect in the temperature of CA6 formation. However, ZnO and TiO2 favoured full CA6 generation at 1400 °C, 200 °C below the reference composition. All analysed systems, besides 2.8Si, showed high porosity (> 80 %), suitable mechanical strength and expansion after firing at 1600 °C for 5 h. Softening temperature evaluation highlighted that ZnO- and TiO2 -containing compositions could be used at higher temperatures than the SiO2 ones. Thus, compositions containing 2.8 mol% of ZnO or TiO2 were evaluated according to their thermal conductivity (keff ), showing lower keff than the reference composition. Therefore, using these mineralizing agents, which are easily available, may provide reductions in the energy input to produce CA6 -containing thermal insulators and benefits to all other required properties.